2020
DOI: 10.3389/fimmu.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Responses to in vivo-Expressed and Stage-Specific Mycobacterium tuberculosis Antigens in Latent and Active Tuberculosis Across Different Age Groups

Abstract: LTBI, while CD14+ TNF-α+ myeloid-like clusters were mostly abundant in adolescent LTBI. Our findings, although limited to a small cohort, stress the importance of assessing broader immune responses than IFN-γ alone in Mtb antigen discovery as well as the importance of screening individuals of different age groups. In addition, our results provide proof of concept showing how unbiased multidimensional multiparametric cell subset analysis can identify unanticipated blood cell subsets that could play a role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Of note, immunisation with BCG_0470 increased the delayed-type hypersensitivity as well as Th1 responses in BCG primed BALB/c mice 46 . All these features, supported by our data in mice and humans 9 , 10 , point to Rv0470c as an attractive BCG booster vaccine candidate when delivered with a properly selected adjuvant 47 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Of note, immunisation with BCG_0470 increased the delayed-type hypersensitivity as well as Th1 responses in BCG primed BALB/c mice 46 . All these features, supported by our data in mice and humans 9 , 10 , point to Rv0470c as an attractive BCG booster vaccine candidate when delivered with a properly selected adjuvant 47 .…”
Section: Discussionsupporting
confidence: 66%
“…Promising TB candidate vaccine antigens first need to be validated in small animal models before they can be selected for evaluation in larger animal models such as non-human primates, and eventually for testing in human clinical trials 11 . Here, we aimed to verify which IVE-TB antigens, previously shown to be recognised by T cells from TB patients and LTBI subjects 9 , 10 , were consistently and broadly recognised during the course of murine Mtb infection in different genetic backgrounds, given the fact that human populations are genetically highly diverse. To include different genetic backgrounds with widely diverse TB-susceptibility phenotypes, we selected C57BL/6, BALB/c and C3HeB/FeJ mice and challenged these with Mtb 20 , 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…120 In an analysis of multiple cytokines after Mtb-antigen stimulation it was found that only TNFα was not significantly more abundant in LTBI. 121 Furthermore, increased single-positive TNFα Mtb-specific CD4 T cells were also found to be highly predictive of active TB. 122 TNFα is primarily produced by macrophages, but can also be secreted by CD4 T cells, and plays a managerial role.…”
Section: Il-17 and Tnf Involvement In Mtb-s Pecifi C Cd 4 T Cell Re S P On S E Smentioning
confidence: 97%
“…As with inflammatory cytokines, TNF α works synergistically with IFN γ in Mtb infection and may be more frequently produced during an active Mtb infection 120 . In an analysis of multiple cytokines after Mtb ‐antigen stimulation it was found that only TNF α was not significantly more abundant in LTBI 121 . Furthermore, increased single‐positive TNF α Mtb ‐specific CD4 T cells were also found to be highly predictive of active TB 122 …”
Section: Il‐17 and Tnf Involvement In Mtb‐specific Cd4 T Cell Responsesmentioning
confidence: 99%